2016
DOI: 10.1080/17415993.2015.1137921
|View full text |Cite
|
Sign up to set email alerts
|

S-Ribosylhomocysteine analogues modified at the ribosyl C-4 position

Abstract: 4-C-Alkyl/aryl-S-ribosylhomocysteine (SRH) analogues were prepared by coupling of homocysteine with 4-substituted ribofuranose derivatives. The diastereoselective incorporation of the methyl substituent into the 4 position of the ribose ring was accomplished by addition of methylmagnesium bromide to the protected ribitol-4-ulose yielding the 4-C-methylribitol in 85% yield as single 4R diastereomer. The 4-C hexyl, octyl, vinyl, and aryl ribitols were prepared analogously. Chelation controlled addition of a carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…In the inhibitor S-homoribosyl-L-cysteine, the carbon (C5)-sulfur bond was replaced by a C5-C6 carbon-carbon bond, which interferes with the cleavage of the carbon-sulfur bond (Alfaro et al, 2004; Figure 2, compound 3). Recently, Chbib et al (2016) synthesized 4-C-Alkyl/aryl-SRH analogs that potentially could inhibit LuxS at the β-elimination step. The substitution of the hydrogen atom at C4 position by alkyl/aryl groups should prevent the abstraction of the C4-proton, which is important for the β-elimination step (Chbib et al, 2016).…”
Section: S-ribosylhomocysteine Lyase Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the inhibitor S-homoribosyl-L-cysteine, the carbon (C5)-sulfur bond was replaced by a C5-C6 carbon-carbon bond, which interferes with the cleavage of the carbon-sulfur bond (Alfaro et al, 2004; Figure 2, compound 3). Recently, Chbib et al (2016) synthesized 4-C-Alkyl/aryl-SRH analogs that potentially could inhibit LuxS at the β-elimination step. The substitution of the hydrogen atom at C4 position by alkyl/aryl groups should prevent the abstraction of the C4-proton, which is important for the β-elimination step (Chbib et al, 2016).…”
Section: S-ribosylhomocysteine Lyase Inhibitorsmentioning
confidence: 99%
“…Recently, Chbib et al (2016) synthesized 4-C-Alkyl/aryl-SRH analogs that potentially could inhibit LuxS at the β-elimination step. The substitution of the hydrogen atom at C4 position by alkyl/aryl groups should prevent the abstraction of the C4-proton, which is important for the β-elimination step (Chbib et al, 2016). Interestingly, these authors suggested that the 4-C-Alkyl/aryl-SRH analogs also could inhibit LuxS by interfering with the dimerization of the enzyme.…”
Section: S-ribosylhomocysteine Lyase Inhibitorsmentioning
confidence: 99%
“…In our program on developing novel inhibitors of S -ribosylhomocysteine (SRH) hydrolase (LuxS; EC 4.4.1.21), which mediates the interspecies quorum sensing among bacteria, 17, 18 we recently applied lithium triethylborohydride (LTBH, Super-Hydride ® ) 19, 20 for the reduction of lactam and lactone analogues of SRH to the corresponding azahemiacetals ( N,O -acetals) 21 or lactols ( O,O -acetals). 22 Although application of LTBH for the reduction of lactams to cyclic hemiaminals (azahemiacetals) is documented, 23, 24 the reduction of lactones to the hemiacetals with LTBH is underdeveloped. In his landmark paper from 1980, 25 Brown reported that LTBH, when used in excess (2 equiv.…”
mentioning
confidence: 99%
“…97,98 Figure 12. Silicon-fluoride acceptors in octreotate 96 32 and thymidine derivatives 99 109 has been utilized for the reduction of lactam (Scheme 10) and lactone analogues of SRH to the corresponding azahemiacetals (N,O-acetals) 110,111 or lactols (O,Oacetals) 112 , a method not extensively explored. Below, the commonly used reducing agents for this type of transformation will be reviewed.…”
Section: Scheme 5 Mechanism Of Isotopic Exchange Reaction Between F mentioning
confidence: 99%
“…121,122 Although the application of LTBH in organic synthesis is well documented, [140][141][142][143] including the reduction of lactams to cyclic hemiaminals (azahemiacetals), including in sugar lactams, 110 the reduction of lactones to the lactols with LTBH is underdeveloped. In the synthesis of 4-C-alkyl/aryl-substituted Sribosylhomocysteine (SRH) analogues, 112 which were prepared by coupling of homocysteine with 4-substituted ribonolactone derivatives, a project that I was involved in, LTBH was used to reduce a series 4-C-alkyl/aryl-modified lactones to their corresponding hemiacetals (Scheme 27). These hemiacetals were then coupled to homocysteine to yield 4C-SRH analogues.…”
Section: Reduction With Ltbh: Rationalementioning
confidence: 99%